2008
DOI: 10.1007/s10157-008-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Fever of unknown origin secondary to type I crescentic glomerulonephritis and anti-SCl 70 antibodies without clinical manifestations of systemic sclerosis

Abstract: A 57-year-old woman presented with fever and cellulitis of the right leg. Urinalysis and kidney function were normal on admission. Cellulitis remitted but fever persisted for six weeks. X-ray imaging, cultures, serological assays for viruses and autoimmunity did not reveal the cause of fever. Unexpectedly anti-Scl 70 (anti-topoisomerase I) antibodies were positive. A skin biopsy ruled out scleroderma. On the fifth hospitalization week kidney function declined in association with hematuria, leucocyturia, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(27 reference statements)
0
1
0
1
Order By: Relevance
“…Topoisomerases play important roles in cell proliferation, differentiation and other life processes, and their expression level increase in multiple solid tumors [14][15][16][17]. More and more studies have shown that dysregulation of topoisomerases associated with many human diseases including tumors [18][19][20]. Selective targeting topoisomerase has always been a hot topic in anticancer therapy [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Topoisomerases play important roles in cell proliferation, differentiation and other life processes, and their expression level increase in multiple solid tumors [14][15][16][17]. More and more studies have shown that dysregulation of topoisomerases associated with many human diseases including tumors [18][19][20]. Selective targeting topoisomerase has always been a hot topic in anticancer therapy [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Llama la atención que en el debut de su enfermedad se hayan detectado anticuerpos anti-MBG en plasma y presencia de anticuerpos anti-MBG subtipos IgG1 e IgG3 en la biopsia renal, mientras que en su recurrencia los anticuerpos anti-MBG fueron persistentemente negativos usando diferentes técnicas (ELISA, Inmunoblot e Inmunoensayo en Clínica Mayo). Tampoco se detectó la presencia de anticuerpos ANCA o anti Scl 70, descritos en otros casos de recurrencia 11,12 .…”
Section: Discussionunclassified